Attachment Styles and Parasocial Relationships among K-Pop Fans in Indonesia - Ni Putu Abigail Firsta S; Krismi Diah Ambarwati (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The Korean Pop phenomenon that is currently happening all over the world including Indonesia has created a new culture among its fans, a culture of building parasocial relationships with their idols. Parasocial relationships that are illusory and one-sided relationships from the fan side only, could be influenced by the fans’ attachment style. This study aims to analyze the relationships between the 4 types of attachment styles: secure attachment style, fearful attachment style, preoccupied attachment style, and dismissing attachment style according to Bartholomew and Horowitz (1991) with parasocial relationships among K-Pop fans in Indonesia. Samples in this study were 378 K-Pop fans from all over Indonesia who were taken with purposive sampling technique. Attachment Style Questionnaire (ASQ) by Oudenhoven, Hofstra, and Bakker (2003) which has been adapted to Indonesian by Fitriana and Fitria (2016) were used as the tool to measure the attachment styles. Meanwhile, parasocial relationships were measured using the Multidimensional Measure of Parasocial Relationships to a K-Pop Idol (MMPR-K-Pop) developed by Garcia, Bjork, and Kazemitabar (2022). The results of this study showed that there are positive correlations between fearful attachment style (r = 0,344; p<0,05) and parasocial relationships and also between preoccupied attachment style and parasocial relationships (r = 0,130, p<0,05), while there are negative correlations between secure attachment style and parasocial relationship (r = -0,150; p<0,05) and also between dismissing attachment style and parasocial relationships (r = -0,157; p<0,05).